THE GREEN ZONE: LEXICAL, PHRASEOLOGICAL, AND CULTURAL PERSPECTIVES - Djalilova Sarvaroy Mekhrojovna; María del Mar Martín Aragón (Bright Mind Publishing, 2025)
This article investigates the notion of the “green zone” (zona verde) within the field of Spanish philology, exploring its lexical evolution, phraseological uses, and cultural significance in Spanish‐speaking societies. By examining dictionary entries, corpus data, and literary texts, the study reveals how the term has shifted from a purely urban‐planning designation to a rich semantic field encompassing environmental discourse, metaphorical extensions, and cultural identity. The analysis highlights the interplay between language, space, and ideology, illustrating how “zona verde” contributes to broader debates on nature, community, and linguistic creativity.
Keywords: Green zone; zona verde; Spanish philology; lexical semantics; phraseology; urban discourse; environmental metaphor; corpus linguistics; cultural semantics; Spanish lexicon.